Verb Phrase Ellipsis and Reflexive Anaphora Resolution in Second Language Acquisition: A Study of Spanish Learners of English - Gandón-Chapela, Evelyn; Gallardo-del-Puerto, Francisco (Miscelánea: A Journal of English and American Studies, 2019)
This paper analyses the choice of sloppy and strict interpretations of reflexive anaphora in verb phrase ellipsis from the perspective of Relevance Theory (RT) (Sperber and Wilson 1986, 1995, 2002, 2008; Wilson and Sperber 2002, 2004). Forty-four Spanish learners of English and 29 native speakers of English were administered two judgement tasks designed to gauge the effect of the Communicative Principle of Relevance on their interpretation of reflexive anaphora in bare, referential and non-referential contexts. Results showed that, in accordance with this principle, the sloppy interpretation is favoured in bare and non-referential contexts, while strict readings prevail in referential contexts, these preferences being less marked for L2 learners than for native speakers. Moreover, the sloppy interpretation is chosen more frequently when native speakers are given a non-referential context, whereas it decreases when L2 learners are provided with the very same context, indicating that the syntax-pragmatics interface makes up an information processing load and acts as a distractor for L2 English learners.